KINETIKA PERUBAHAN KADAR 5-Hydroxymethyl -2-Furfural (HMF) BAHAN MAKANAN BERPATI SELAMA PENGGORENGAN [Kinetics of Changes of 5-Hydroxymethyl-2-Furfural (HMF) Content Of Starchy Food during Frying] - Supriyanto ,; Budi Rahardjo; Y. Marsono; Supranto , (Jurnal Teknologi dan Industri Pangan, 2006)
Cooking of the starchy foods at high temperature can result in formation of  5-Hydroxymethyl-2-Furfural (HMF) compound. The HMF content of starchy foods changes during the heat treatment in the frying process. The rate of change of the HMF content during frying depends on oil temperature, initial water content and the amylosa – amylopctin ratio of the material. The objective of the research was to study the kinetics of HMF change in the starchy foods during frying process. The change of the HMF content was assumed following by the first order kinetic model.                The samples used in the experiment were the dried dough corn powders. The dough was made of a mixture of two varietes of corn with different amylosa – amylopectin content, with variation on the composition of the mixture. Bisma variety was used as the high amylosa ( low amylopectin) and Pulut (waxy) was used as the low amylosa (high amylopectin).The samples were fried in palm oil using    a deep fat frying method with variation of oil temperature, initial water content and content of amylosa – amylopektin  ratio. The HMF of the fried product was extracted with absolute ethanol and the extracts were determined by UV-Vis Spectrophotometer at 281,5 nm. The result indicated that the rate of change of the HMF content in corn increased with the increasing oil temperature and amylosa content and decreased with initial water content.                 The model applied to the changing  on HMF content  showed that the equation :  Xhmf =  A (1– B e-km t ) (with Xhmf = the HMF content; km = The rate of the HMF changing; t = frying time; A and B = the contsnts) can be used  for estimation  the change of the HMF content of  the corn fried product during the frying process